A time study of the activities and workload of the rural health physician - Orduna, Beatriz C.
This study was made to provide a baseline data and other information for other related studies to help guide administrators and Rural Health Physicians with respect to wise investments of working time and effort.
Thesis (Master of Public Health)--University of the Philippines Manila, 1966
Keywords: Rural health clinics; Rural health services; Rural health physicians